Pesantren di tengah perubahan sosial - Imam Moedjiono (EL-TARBAWI, 2002)
It’s interesting to discuss and research pesantren as Islamic Education Institution from many perspectives. Especially in social economic and politics change which happen in Indonesia. Many activities are holding by pesantren, which indicate pesantren pays attention to Moslem community empowerment, in order to they do not collapse to the worst condition. Moreover pesantren is potential to anticipate many situations proactively to aim better condition of ummat in the future.Key Word: Islamic education institution, social-economic changes